Users' Guide to the SDR : A Manual of Transactions and Operations in Special Drawing Rights. (Manuals and Guides, 1995)
This guide explains to participants in the Special Drawing Rights Department and prescribed holders of SDRs the transactions and operations permitted under the IMF's Articles of Agreement and applicable decisions of the Executive Board.